The properties on differential-difference polynomials - Cao, T. B.; Liu, K.; Liu, X. L. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
The main aim of this paper is to improve some classical results on the distribution of zeros for differential polynomials and differential-difference polynomials. We present some results on the distribution of zeros of [f(z)^nf(z + c)]^(k) α (z) and [f(z)^n(f(z + c) f(z))]^(k) α (z) and give some examples to show that the results are best possible in a certain sense.